The Influence of Locus of Control and Complexity of Audit Tasks on the Performance of Internal Auditors - Bulan Rahmayani Eifeli Sulla (Journal of Business, Accounting and Information Technology, 2026)
This study examines the influence of locus of control and audit task complexity on the performance of internal auditors at the Regional Inspectorate of Kupang Regency. In the context of increasing demands for good governance, internal auditors play a critical role in ensuring accountability, transparency, and effectiveness in public sector management. This research adopts a quantitative approach with an associative-causal design. Data were collected through questionnaires administered to 34 internal auditors using a census sampling technique. The data were analyzed using multiple linear regression supported by validity, reliability, and classical assumption tests. The results indicate that locus of control has a positive and significant effect on auditor performance, suggesting that auditors with a stronger internal control orientation tend to demonstrate higher motivation, responsibility, and effectiveness. Conversely, audit task complexity has a negative and significant effect, indicating that higher complexity increases cognitive burden and reduces performance quality. Simultaneously, both variables significantly influence auditor performance, with a coefficient of determination of 51%. This study highlights the importance of balancing psychological factors and organizational conditions to improve auditor performance. The findings provide practical implications for strengthening internal audit effectiveness through capacity building and better workload management in local government institutions